(untitled) (Latakia University Journal -Biological Sciences Series, 2023)
This study includes an update of the list of decapod crustaceans in the Syrian marine waters that form part of the eastern basin of the Mediterranean Sea, with the addition of two new species to the list of biodiversity of this important animal group. The existence of these two species, Macropodia rostrata (Linnaeus, 1761) and Parthenope massena (Roux, 1830), has been documented through collections for years, with an accurate description and notes on their geographical distribution. The results of searches and investigations showed that the total number of marine decapods known in Syria reached 142 species, of which 34 were alien species that arrived in our sea waters in different ways, but most of them came through the Suez Canal (Lessepsians species). The marine decapod fauna of Syria belongs to the Mediterranean region, and appears closely related to the tropical fauna. The species of this group are divided into three categories according to their origins: the first is the native species that are endemic to the Mediterranean and not encountered elsewhere (11 species), while the second category includes the species that are found in both the Mediterranean and the Atlantic Ocean (97 species). ). The third category consists of species that trace their origins to the fauna of the Indian Ocean, the Pacific Ocean, and the Red Sea, and they entered the Mediterranean through the Suez Canal (34 species).